THE INFLUENCE OF PRECEPTORSHIP TRAINING ON THE GUIDANCE QUALITY TOWARDS CLINICAL PRACTICE STUDENTS - Turambi, Aloysius; Musharyanti, Lisa (Jurnal Keperawatan Respati Yogyakarta, 2021)
The preceptorship model has been widely used in clinical nursing education to achieve clinical students’ competence.Although preceptorship is the core of clinical education, it also requires restructuring and support in its implementation so that preceptorship training develops. Preceptorship training has an important effect on competence, clinical skills, and satisfaction of the preceptor in guiding nursing students, but not all preceptor nurses are trained to perform this complex role.This study aims to identify the effect of preceptorship training on the guidance quality of clinical practice students.This study is a literature review, accessed from internet database searches i.e. Google Scholar, Pro Quest, and Sciencedirect with the keywords preceptorship, preceptorship training, preceptorship and clinical practice. From the Google Scholar database, 480 articles were found, 365 articles from Pro Quest and 327 from Sciencedirect. After going through the screening process and eligibility, 7 articles fit the inclusion criteria and were analyzed. The results showed that there are 4 parts that result from preceptorship training and affect the guidance quality of clinical practice students to increase knowledge, clinical skills, and confidence in the nursing process, improve communication skills, provide positive support to students, and connect the gap between theory and practice. Keywords: Preceptorship; Preceptorship Training; Preceptorship And Clinical Practice